2002
DOI: 10.5194/angeo-20-1959-2002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical simulation of O<sup>+</sup> and H<sup>+</sup> densities in the Indian low latitude F-region and comparison with observations

Abstract: Abstract. The O + and H + ion density distributions in the Indian low latitude F-region, within ±15 • magnetic latitudes, are simulated using a time dependent model developed on the basis of solution of the plasma continuity equation. The simulated ion densities for solar minimum June and December solstices are then compared with ionosonde observations from the period 1959-1979 and measurements made by the Indian SROSS C2 satellite during 1995-1996 at an altitude of ∼ 500 km. The simulated O + density has a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Truhlik et al (2005) discussed solar activity in the global topside ion composition based on satellite data from OGO-6, AE-C, AE-E and IK-24 during the period from the late 1960s to the early 1990s. Bhuyan et al (2002) compared the results with the density measurements made by the Indian SROSS-C2 satellite. Bhuyan and Borgohain (2005) studied diurnal, seasonal and latitudinal variation of ion concentrations as obtained from the SROSS-C2 satellite over Indian low and equatorial latitudes during solar minima.…”
Section: Introductionmentioning
confidence: 97%
“…Truhlik et al (2005) discussed solar activity in the global topside ion composition based on satellite data from OGO-6, AE-C, AE-E and IK-24 during the period from the late 1960s to the early 1990s. Bhuyan et al (2002) compared the results with the density measurements made by the Indian SROSS-C2 satellite. Bhuyan and Borgohain (2005) studied diurnal, seasonal and latitudinal variation of ion concentrations as obtained from the SROSS-C2 satellite over Indian low and equatorial latitudes during solar minima.…”
Section: Introductionmentioning
confidence: 97%
“…In June the neutral particles moves to north at northern hemisphere and to south direction over southern hemispheres, while in December, the neutral wind mainly pointed to east-west and northward direction at middle and low latitudes over both hemispheres. Bhuyan et al (2002) gave the diurnal variations of neutral wind velocity for December and June solstice at three geomagnetic latitudes from the equation of Chauhan and Gurm (1980), in which the neutral wind velocity direction were opposite to each other at 10°N and 10°S in June, but they showed similar direction in December, both pointing to the north at LT10:00. West and Heelis (1996) analyzed the longitudinal modulations of ion compositions at topside ionosphere by meridional and zonal neutral winds, and they demonstrated that the summer to winter meridional winds in solstice season mainly regulate the F peak height, with the zonal winds enhancing or opposing the effects of the meridional winds at the longitude 150 -270°E and 300 -360°E with significant magnetic declination there.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide reasonable full diurnal coverage of the model values within a specified altitude and latitude region, the model equation needs to be solved along many tubes of plasma . The procedure adopted is similar to that adopted by Bhuyan et al (2002a) except for the fact that the vertical drift is a function of height in the present simulation and the number of field lines suitably increased. A two-dimensional grid of points in altitude and latitude is produced for every 4 min interval of local time, from which the data at any local time, latitude and height can be recovered taking into consideration the drift of plasma at each time interval.…”
Section: Electron Densitymentioning
confidence: 98%
“…Recently, Pavlov et al (2004) have reported results from comparison of measured and modeled electron densities, and electron and ion temperatures for magnetically quiet and moderate solar activity conditions at locations close to the geomagnetic equator and equatorial anomaly crests along 201°geomagnetic meridian. Bhuyan and Kakoty (2001a,b) and Bhuyan et al (2002a) had simulated the ion density distribution in the topside F-region of the Indian low latitude ionosphere for solar minimum equinoctial conditions and compared the results with the density measurements made by the Indian Stretched Rohini Satellite Series (SROSS C2). However, model simulations of both density and temperature in the F-region of the Indian zone ionosphere have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%